MANAJEMEN GURU DALAM PENUNTASAN WAJIB BELAJAR PENDIDIKAN DASAR Strategi Manajemen Guru Berorientasi Pemerataan Akses dan Peningkatan Mutu Pendidikan Dasar di Kabupaten Kuningan - Marfu, Kuswandy Achmad (IKIP Siliwangi Bandung, 2012)
The efforts to accelerate finishing the compulsory of basic education in Kuningan Regency - one of the regencies located in West Java Province - related to three important aspects. First, the compulsory of basic education including equality and equity. Second, to finish the compulsory of basic education requires good commitment of the Regency especially in developing strategic management based on the existing conditions. Third, to finish the compulsory of education requires comprehensive efforts including the improvement of the role of the teachers in field of basic education itself. The improvement itself should cover : (1) all of the teachers in basic education field; (2) the understanding of the minimum academic qualification of teachers based on the Law of Teacher and Lecturer and the governmental rules especially the Standards of National Education. Based on the issue and identification, the writer focuses the study on “How to develop the management of teachers in basic education field is able to finish the Program of the Nine Year Compulsory Basic Education in Kuningan Regency?” This study uses the qualitative approach, by gathering information through interview, observation, and documentary study. The validity of the data is tested by member check, triangulation, and audit trail; then analyzed by analysis techniques. The findings of the study are as follow. First, the content of vision of The Education Board as the main reference in finishing the basic education program reflects the commitment of the political will which has competitive value. Second, the program of finishing the basic education in Kuningan Regency is effective enough based on the achievements of the attainment effects of education in the form of “ Gross Enrollment Rate (GER)/Angka Partisipasi Kasar (APK),Net Enrollment Rate (NER)/Angka Partisipasi Murni (APM), drop out and “School Enrollment Rate (SER)/Angka Mengulang”. Third, the management of teachers in the field of basic education has good impacts. This is withdrawn based on : 1) the additional number of the teachers appointed to be civil servant (Pegawai Negeri Sipil); 2) the additional number of the teacher whose educational background are suitable with the subject matter they teach, this is the result of special program like special training for teachers or giving scholarship to the teachers who are attending further education. Fourth, the program of finishing basic education and the management of the teachers has significant effect to the quality of basic education in Kuningan Regency. This proved by achieving 98.72 of the efficiency of education for elementary school; 97.33 for junior high school. The achievement effect proved by the graduate number reaches 97.44% for MTs and 97.22% for Junior High School (SMP). Fifth, the hypothetic model of the management of the teachers in the basic education field has significant effect to the quality of basic education in Kuningan Regency. This covers the components of vision, comprehensive planning, the competence of the superintendent in the basic education field, the competence of teachers in the basic education field. All of the components focused on the accessibility and the quality of the ongoing of the basic education. This study recommends that the development of the academic qualification and the competence of the teacher in the basic education field will give good significant to the service of basic education for the society. The competence itself refers to the competences based on the laws and rules, besides, considered on the geographical, economic, social, cultural, technical factors. The Alternative of strategy proposed in this study, needs to be followed up in implementation stage, in order to recover the strengths and weaknesses. Therefore, the studies on the management of the teacher in the basic education field is still available.